Segurança e tolerabilidade do tratamento medicamentoso do transtorno de déficit da atenção com hiperatividade em adultos: revisão sistemática e meta-análise - Oliveira , Danielly Chierrito de (2016)
Introduction: The Attention Deficit Hyperactivity Disorder (ADHD) is considered a neurobiological disorder characterized by symptoms of inattention, disorganization, hyperactivity and impulsiveness, and is diagnosed in about 2.5% to 3.4% in adults individuals. The choice of appropriate medical treatment should be based on reliable and quality evidences. Objectives: Gather evidences of safety and tolerability of the drugs used in the treatment of ADHD in adult patients without comorbidities associated. Methodology: A systematic review was conducted in the databases Medline, Scopus, Science Direct, The Cochrane Library, Web of Science, Scielo, Psyc Info and International Pharmaceutical Abstracts and updated in June 2016. We included randomized, double-blind and parallel trials, which evaluated the safety and tolerability of the drugs used in the treatment for ADHD. The adverse events reported with the use of atomoxetine were grouped by systems, according to the changes induced in individuals in accordance with MedDRA® dictionary. For traditional meta-analysis of dichotomous outcomes were calculated effect of measures such as odds ratio (OR) with 95% confidence intervals, using the Mantel-Haenszel statistical method. Continuous outcomes were analyzed using standardized mean difference ± standard deviation, considering the statistical method Mean difference. Regarding the network meta-analysis, we used the Bayesian statistical model, adjusted chain Monte Carlo Markov. We considered effect of measures as OR with 95% credibility intervals and statistically significant p <0.05. Statistical analyzes were conducted with the assistance of Review Manager software, version 5.3 and Addis software, version 1.16.5. Results: In the first chapter, we evaluated safety and tolerability outcomes of treatment of ADHD with atomoxetine compared to placebo, from traditional meta-analysis, and chapter 2 safety outcomes related to five drugs through network meta-analysis. It was identified a total of 7487 articles and, from these, 6 (n = 2481) and 10 (n = 3006) were included for analysis in chapters 1 and 2, respectively. Considering the outcomes of the first chapter, which were grouped by system, most meta-analyzes of adverse events related to the nervous system, psychiatric, gastrointestinal, sexual, metabolic and general, as well as security considering vital signs showed difference statistically significant in favor of placebo. The tolerability outcomes showed that the highest number of abandonment of treatment by adverse events, statistically significant, occurred in the treated group (OR 0.37 [95% CI 0.23, 0.59]) and lack of efficacy in the placebo group (OR 1.86 [95% CI 1.26, 2.75]). Through the network meta-analysis, outcomes analyzed in chapter 2, statistically significant differences were observed in comparisons: Appetite decreased between atomoxetine and placebo (OR 0.15 [95% ICr 0.05; 0.38]) and mixed amphetamine salts extended-release and placebo (OR 0.06 [95% ICr 0.00; 0.51]); insomnia between atomoxetine and placebo (OR 0.48 [95% ICr 0.27; 0.88]) and mixed amphetamine salts extended-release and placebo (OR 0.23 [95% ICr 0.06, 0.76] ); somnolence between atomoxetine and methylphenidate OROS (OR 0.24 [95% ICr 0.06; 0.97]) and libido decreased between atomoxetine and placebo (OR 0.28 [95% ICr 0.08, 0.90]). Conclusions: It was possible to generate evidence on the safety and tolerability profile of drugs for ADHD, pointing out that atomoxetine compared to placebo is more associated with adverse events and therefore higher abandonment of treatment. Another aspect that evaluated the tolerability of these drugs was the abandonment for lack of efficacy, where the placebo group presents this outcome more often statistically confirmed. From meta-analysis network (chapter 2), it became clear that atomoxetine and mixed amphetamines salts extended-release are more involved with adverse events of appetite decreased and insomnia, and atomoxetine with somnolence and libido decreased. There are still some gaps to be filled and further studies involving these drugs and pharmacoeconomic analysis should be conducted to support health decision-making, directing for choosing the best treatment option.